Pengaruh CR, DAR, Dan TATO Terhadap ROA Pada PT. Bukit Asam Tbk Periode 2010-2022 - Ghina Khansa, Sherina; Susilo Jahja, Adi (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Company performance is displayed through financial reports. Company success can also be measured using financial ratios. In accordance with industry standards, a good performing company must have an average ROA value of 30%. This research aims to analyze the influence of the current ratio (CR), debt to asset ratio (DAR), total asset turnover (TATO) and return on assets (ROA) on the company PT. Bukit Asam Tbk (PTBA) for the 2010-2022 period. This research was conducted using descriptive quantitative methods using secondary data in the form of PTBA financial results reports. The analysis techniques used are descriptive analysis, hypothesis testing, and multiple linear regression testing using IBM SPSS 23. The results of the research show that the current ratio (X1) partially has no significant effect on ROA (Y), the debt to asset ratio (X2) partially does not have a significant effect on ROA (Y) and total asset turnover (X3) partially has a significant effect on ROA (Y) in PTBA for the 2010-2022 period. CR, DAR, TATO stimulantly have a positive and significant effect on return on assets (Y) in PTBA for the 2010-2022 period with a value of with a significant value of 0.035.